FTIR AND NMR STUDIES OF ADSORBED TRITON X-114 IN MCM-41 MATERIALS - Paulina Taba (Universitas Gadjah Mada, 2009)
One source of water pollutions is caused by the high use of surface-active agents (surfactants) by industries and households. As a consequence, it is required to remove such substances from the environment One of the important and widely used methods for removal of substances from solution is adsorption. In this research, MCM-41 and its modification MCM41-TMCS were used to adsorb nonionic surfactant, Triton X-114. FTIR and NMR methods were used to study the interaction between the surfactants and the adsorbents. MCM-41 was synthesized hydrothermally at 100 oC and its modification was conducted by silylation of MCM-41 with trimethylchloro silane (MCM41-TMCS). Both unmodified and modified MCM-41 can adsorb the surfactant. The amount adsorbed in the unmodified material is higher than that in the modified one. The interaction of Triton X-114 with MCM-41 was hydrogen bonding between the silanol groups in MCM-41 and hydroxyl groups of Triton X-114. For modified samples, Triton X-114 interacted with alkylsilyl groups mostly through hydrophobic interaction. It is more likely that the interaction was through C12, C13, C26 and C27 of Triton X-114.